PERANCANGAN DAN IMPLEMENTASI ROBOT EXPERT ADVISOR (EA) BERBASIS BAHASA PEMROGRAMAN MQL 5 MENGGUNAKAN STRATEGI EMA DAN RSI - Ahmad Syahrul Maskuri; Wincoko Wincoko; Yanuar Sinarta (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
The development of technology in forex trading has encouraged the use of automated systems to assist analysis and decision-making. However, traders still face challenges in technical analysis, emotional control, and time limitations, making an automated system for executing trades necessary. This study aims to design and implement an Expert Advisor (EA) based on the MQL5 programming language using Exponential Moving Average (EMA) and Relative Strength Index (RSI) indicators. The method used is the waterfall model, which includes analysis, design, implementation, and testing stages. The system was tested using historical EUR/USD data on the MetaTrader 5 platform. The results show that the system generated 125 trades, consisting of 48 profitable and 77 losing trades, with a win rate of 38.40%. The system produced a profit of 21.29 USD with a maximum drawdown of 0.90%. Based on general trading performance standards, this win rate is considered relatively low; however, it is still acceptable due to the low drawdown, indicating that the system maintains controlled risk despite its suboptimal signal accuracy. In conclusion, the developed EA is capable of operating properly and generating profit, but further improvement is needed, particularly in enhancing signal accuracy to achieve better performance.